Two sodium pumps in the hepatopancreas of the intertidal euryhaline crab Neohelice granulata: Biochemical characteristics and differential modulation after feeding - Méndez, Eugenia (2018)
No study has been done on the existence, biochemical characteristics, and modulation of K+-independent ouabain-insensitive Na+ ATPase activity (the second sodium pump) in the digestive tract of intertidal euryhaline crabs and moreover on the coexistence and modulation under distinct physiological and (or) environmental conditions of different sodium pumps. We determined the occurrence, characteristics, and responses at different times (0, 1, 24, 48, and 120 h) after feeding upon distinct salinities of Na+ ATPase activity and Na+/K+ ATPase in the hepatopancreas of Neohelice granulata (Dana, 1851), which is a model species. The stimulation by Na+ under total inhibition of Na+/K+ ATPase activity revealed the occurrence of Na+ ATPase activity that was totally inhibited by 2 mmol·L–1 furosemide, exhibits Michaelis–Menten kinetics for ATP (apparent Km = 0.52 ± 0.16 mmol·L–1), and highest activity at around pH 7.4. In crabs acclimated to 35 psu (osmoconforming conditions), Na+ ATPase activity was highly increased (about 15-fold) (532 ± 58 nmol Pi·mg protein−1·min−1) in the hepatopancreas 48 h after feeding. In 10 psu (hyper-regulating conditions), Na+ ATPase activity decreased in the hepatopancreas 24 h after feeding (7 ± 9 nmol Pi·mg protein−1·min−1) and recovered initial values after 48 h (24 ± 35 nmol Pi·mg protein−1·min−1). Unlike Na+ ATPase, Na+/K+ ATPase activity did not change after feeding at any salinity, suggesting the specific modulation of the second sodium pump and its role in postprandial adjustments in the hepatopancreas.